SiRNA-mediated knockdown against NUF2 suppresses tumor growth and induces cell apoptosis in human glioma cells - Huang, S-K.; Qian, J-X.; Yuan, B-Q.; Lin, Y-Y.; Ye, Z-X.; Huang, S-S. (Cellular and Molecular Biology, 2014)
Glioma is one of the most commonly malignant brain tumors. Current therapies for glioma have failed to achieve satisfactory results, which necessitates the development of novel molecular therapies. In the current study, we aimed to investigate the role of NUF2 (Ndc80 kinetochore complex component) in glioma cell growth and assessed the possible mechanisms underlying NUF2-mediated glioma development. The lentivirus-based short hairpin RNA-expressing vectors were constructed and transfected into U87 and U251 cells. Real time PCR and western blot were performed for expression level determination. Annexin V-FITC/PI flow cytometric assay was conducted to determine apoptotic cell proportions. Cell viability in vitro and tumorgenic ability in vivo were assessed by MTT assay and a nude mouse xenograft, respectively. We found that NUF2 was overexpressed in glioma tissues and differentially expressed in a series of glioma cell lines. Depletion of NUF2 by short-hairpin RNA inhibited cell growth in vitro and in vivo. Furthermore, NUF2 depletion-induced growth inhibition was associated with cell cycle arrest and apoptosis. Aberrant expressions of cell cycle regulators and apoptosis-related proteins further confirmed that NUF2 depletion induced cell cycle arrest and apoptosis. In all, our results indicate that siRNA-mediated knockdown against NUF2 may be a promising therapeutic method for the treatment of glioma.